Impact of Golden Banana Puree (Musa acuminata) Enrichment on the pH, Lactic Acid Bacteria Count, and Viscosity of Kefir - Rasbawati, Rasbawati; Fitriani, Fitriani; Puspitarini, Oktavia Rahayu; Novieta, Intan Dwi; Irmayani, Irmayani (Jurnal Agripet, 2024)
The addition of golden banana puree (Musa acuminata) as a prebiotic has been hypothesized to enhance the growth of lactic acid bacteria in kefir. This study aimed to determine the effects of adding golden banana puree on the pH value, total lactic acid bacteria (LAB) count, and viscosity of kefir. The experiment was conducted using a Completely Randomized Design (CRD) with four treatments and three replications. The treatments included the addition of 0% (P0), 6% (P1), 8% (P2), and 10% (P3) banana puree. The observed variables were pH value, total LAB, and viscosity. Data were analyzed using Analysis of Variance (ANOVA), followed by Duncan's Multiple Range Test (DMRT) when a significant treatment effect was detected. The results indicated that the addition of golden banana puree had a very significant effect (P0.01) on the pH value, total LAB count, and viscosity of kefir. The study concluded that increasing the concentration of golden banana puree leads to a higher total LAB count and viscosity, while inversely lowering the pH value.